Analisis Sifat Mekanik Material Chopped Strand Mat Fiber Composite Perahu Fiber Berbahan Dasar Tripleks - Badaruddin Anwar; Djuanda Djuanda; Samnur Samnur (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the mechanical properties of chopped strand mat fiber composite fiber boat made from plywood. This research consisted of 3 mm Triplex material with standard ASTM D3039 specimens consisting of 5 samples, Chopped Strand Mat 450 Fiber, 1 kg, catalyst, and resin. Samples were tested mechanically by using a tensile test machine A & D Tensilon Machine Type RTF-2425 with a maximum capacity of 250 kN, ie composite materials which amounted to 5 samples according to ASTM standards. The mechanical properties of composite materials illustrate the strength and toughness, the tensile strength of the chopped strand mat composite fiber material in the manufacture of triplex-based fiber composite boats is 113,676 MPa. There is a difference in the tensile strength of 33% of the chopped Strand Mat Fiber Composite material made from plywood and Chopped Strand Mat Fiber Composite material made from fiber plates.